Laser acupuncture in the energetic regulation of temporomandibular dysfunction: a randomized controlled trial (Revista da Faculdade de Odontologia - UPF, 2025)
The regulation of energy before clinical interventions can enhance therapeutic outcomes. While laser acupuncture has been shown as a complementary approach in dental care, no studies have assessed its potential to regulate energy in individuals with temporomandibular dysfunction (TMD). This study aimed to determine whether laser acupuncture promotes energetic regulation in patients with muscular-origin TMD. A blind, randomized clinical trial was conducted with 48 participants experiencing both energy imbalance and TMD-related pain. Subjects were distributed into four groups: acupuncture (A), laser (L), and their respective placebos, PA and PL. Group A received traditional acupuncture with needles; group L underwent low-level laser therapy; placebo groups had acupoints identified but without active stimulation. The Ryodoraku device, which evaluates 24 acupuncture points on the 12 meridians, was used to measure energy levels to detect regulation.Â  Statistical analysis was performed using repeated-measures ANOVA, with significance set at p